Pometia pinnata in Pharmaceutical Research: Bioactivity, Mechanisms, and Formulation Prospects - Sulastri, Lela; Sugihartini, Nining; Efiana, Nuri Ari (Sciences of Pharmacy, 2025)
A literature review was conducted to gather information on the pharmacological properties and pharmaceutical dosage forms made from the Matoa plant (Pometia pinnata). The review aimed to provide a basis for further research and explore the potential of Matoa in the health sector. The method involved searching electronic media platforms, specifically Google Scholar, PubMed, and Open Knowledge Maps, using targeted keywords such as "Matoa,” "Pometia pinnata,” "Matoa preparation formulation,” "Pometia pinnata pharmaceutical preparation,” "Preparation of Pometia pinnata," and "Function of Pometia pinnata." The inclusion criteria included original research, full-text articles, and open-access journals, all published within the last 10 years, in both Indonesian and English. After screening, 64 articles were identified from the 185 search results. The review revealed that various parts of the Matoa plant, including leaves, fruit, stem bark, fruit peel, and roots, possess pharmacological properties such as antibacterial, analgesic, antioxidant, sunscreen, anticancer, antidiarrheal, anti-HIV, anti-obesity, diuretic, nephrotoxic, and antihypertensive activities. Additionally, various pharmaceutical dosage forms containing Matoa were studied, including topical preparations such as lotions, creams, liquid soap, and body scrubs, as well as oral preparations like effervescent powders, herbal drinks, and jelly candies. The review suggests that numerous research opportunities remain to further explore the potential of Matoa in the pharmaceutical and healthcare fields, as well as to develop innovative dosage forms for optimal results.